Permutation tests for centre effect on survival endpoints with application in an acute myeloid leukaemia multicentre study. (28th March 2014) - Biard, L.; Porcher, R.; Resche‐Rigon, M.
<x xml:space="preserve">Abstract</x> When analysing multicentre data, it may be of interest to test whether the distribution of the endpoint varies among centres. In a mixed‐effect model, testing for such a centre effect consists in testing to zero a random centre effect variance component. It has been shown that the usual asymptotic χ2 distribution of the likelihood ratio and score statistics under the null does not necessarily hold. In the case of censored data, mixed‐effects Cox models have been used to account for random effects, but few works have concentrated on testing to zero the variance component of the random effects. We propose a permutation test, using random permutation of the cluster indices, to test for a centre effect in multilevel censored data. Results from a simulation study indicate that the permutation tests have correct type I error rates, contrary to standard likelihood ratio tests, and are more powerful. The proposed tests are illustrated using data of a multicentre clinical trial of induction therapy in acute myeloid leukaemia patients. Copyright © 2014 John Wiley & Sons, Ltd.